As contradições do espaço público na cidade de São Paulo: uma abordagem a partir do Minhocão e seus diferentes usos - Oliveira, José Carlos de (2016)
This essay analyzes the different “appropriations” of Minhocão’s area, built as a road axis to cars quick circulation and, more recently, appropriated for diverse usages, such as leisure, mainly. São Paulo’s capitalist urbanization reached its peak in the 70s, mainly with the market opening to cars industry. Nevertheless, since 1930, the implementation of an urban management and planning model has produced deep socio-spatial impacts, such as a fragmented urban web, the irradiation of urban areas to peripheral regions, the public area privatization, the growth of socio-economic inequalities and spatial segregation. Minhocão, built from this model, has become an emblematic piece of urban space submission to highways culture, ideology that justifies the investment of most of public resources in infrastructure towards individual transportation. By the end of the 80s decade, with the inauguration of the new capitalism era, there were changes in the production system, however, the socio-spatial impacts persisted in even more ample scales. In this period, the ludic “appropriation” of Minhocão on Sundays and holidays started. It reunites a variety of actors to the enjoyment of cultural events, sports practice and other leisure activities. On one hand, the ludic “appropriation” enables the public space redemption as a place for social conviviality and promotes the right to the city. On the other, it can also reproduce the capitalist city’s demands. In order to develop this main hypothesis, we started from the critic-dialectic benchmark and empiric research, of ethnographic bias, with Minhocão’s users during the ludic activities. The authors who supported this analysis of public space and the contradicting aspects of its different usages, in micro or macro structural scope, share a common objective: the public space transformation, however resulting from diverse research fields: architecture and urbanism, philosophy, urban sociology, history and politics. The result of the theoretical analysis and the empiric research indicate that Minhocão reproduces the capitalist city’s demands, however, as a place which reunites different groups for ludic activities, can also promote new “appropriation” ways of the public space and the citizenship participation in the diverse social actors